Progress of research on core outcome sets in cancer clinical trials (肿瘤领域核心结局指标集研究进展) - MA Lifang (马丽芳); WEI Huan (未欢); DONG Jia (董佳); LIU Hainan (刘海楠); WEI Xiuling (魏秀玲) (中西医结合护理)
Core outcome sets are developed with the idea to solve problems in most research settings, such as wide variations in reported outcomes of included studies and selective reporting. Most core outcome sets focused on a specific cancer, however the research status and progress of core outcome sets in cancer clinical trials is still unclear. This paper reviewed changes in the number of studies, specific content and methodological advances, and provide a clear overview of research in such area. (现阶段临床研究中存在一些问题可以通过建立核心结局指标集来解决, 如同类研究中常见的纳入研究的结局指标间差异大的问题以及选择性报告结局的现象。核心指标集研究在肿瘤领域研究最为广泛, 但目前对肿瘤领域核心结局指标集的研究现状及进展尚不明确。本研究对肿瘤领域核心结局指标集研究的数量变化、具体内容及方法学的进展展开综述, 以明确该领域研究概况。)